Regional flow analysis for the valle del cauca region in colombia (1996)
Flow frequancy analysis of high and low flows is curry out by using the regional Probability Weighted Moments (PWM) algorithm. The distributions fitted to the región area: General extreme value (GEV), Wakeby, Extreme value type 1 (EVl) or Gumbel and Weibull (two or three parameters) distribution. In order to selecte the distribution appropite for each series for test of goodness of fit were carry out, manely, chi square, 'DMAX ' goodness of ifit, probability plot criteria and a graphical test base on Montecarlo simulation. The selection of the distribution is made to depend on the performance of the distributions under tests over all test. The distributions selected for annnual máximum flow series is the EVl distribution while the GEV distribution is selected for the annual minimum flow series.